2018
DOI: 10.1002/icd.2099
|View full text |Cite
|
Sign up to set email alerts
|

Unsociability and socio‐emotional functioning in young Chinese children: A short‐term longitudinal study

Abstract: The goal of this study was to examine longitudinal associations among unsociability and indices of socio‐emotional functioning in a sample of young Chinese children. Participants were N = 360 children (Mage = 4.72 years, SD = .67) recruited from kindergarten classes in an urban area of China. Assessments of unsociability and adjustment were obtained at 2 time points (separated by 1 year) using multiple source assessments (maternal reports, child interviews, teacher ratings). Among the results, unsociability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(59 reference statements)
2
7
0
Order By: Relevance
“…Teachers also completed the Chinese version of Child Behavior Scale (CBS; Ladd and Profilet, 1996 ; Zhu et al, 2018 ). Of particular interest were subscales assessing asocial behavior (six items, e.g., “likes to be alone, withdraws from peer activities”; ɑ = 0.87), and peer exclusion (seven items, e.g., “not welcomed by other children”; ɑ = 0.86).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers also completed the Chinese version of Child Behavior Scale (CBS; Ladd and Profilet, 1996 ; Zhu et al, 2018 ). Of particular interest were subscales assessing asocial behavior (six items, e.g., “likes to be alone, withdraws from peer activities”; ɑ = 0.87), and peer exclusion (seven items, e.g., “not welcomed by other children”; ɑ = 0.86).…”
Section: Methodsmentioning
confidence: 99%
“…Items were rated on a three-point scale (from 1 = “doesn’t apply” to 3 = “certainly applies”). The CBS has been shown to be reliable and valid in young Chinese children ( Zhu et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Presently, there are few longitudinal studies on unsociability in China, especially with respect to those that explore the preschool stage, which is a critical period for individual development (Xiao et al, 2021; Zhu, Baldwin, et al, 2018; Zhu, Wang, & Li, 2018). Accordingly, this study explores the extent to which unsociability predicts incremental changes in maladaptive parenting and peer exclusion over time in a sample of preschool‐aged children from urban Mainland China.…”
Section: The Present Studymentioning
confidence: 99%
“…Accordingly, this study explores the extent to which unsociability predicts incremental changes in maladaptive parenting and peer exclusion over time in a sample of preschool‐aged children from urban Mainland China. Moreover, only a few studies have looked at the relationship between unsociability and adjustment outcomes in Chinese preschoolers and found no gender difference (Li et al, 2016; Zhu, Baldwin, et al, 2018; Zhu, Wang, & Li, 2018). Although it is not the primary focus of the current study, we investigated potential gender differences.…”
Section: The Present Studymentioning
confidence: 99%
“…Therefore, intentionally removing oneself from the peer group is perceived as anti‐collective, selfish, and abnormal (Chen, 2009). Research on unsociability among Chinese children has revealed that unsociability is associated with a host of social and psychological issues, some of which are more pronounced in boys as compared to girls (Coplan et al, 2016; Liu et al, 2014, 2015, 2017; Zhang & Eggum‐Wilkens, 2018a; Zhu, Baldwin, Li, Xie, & Coplan, 2018). For example, Zhang and Eggum‐Wilkens (2018b) found that unsociable Chinese early adolescents experienced high levels of peer exclusion.…”
Section: Introductionmentioning
confidence: 99%